The first step in simplifying is to apply that outer exponent of
to each factor inside the parentheses.
![\left(8\cdot x^6\right)^(2/3) = \left(8\right)^(2/3) \cdot \left(x^6\right)^(2/3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/xngvrhq0jqspguax1dpbuofajxazui02k4.png)
Now using the concept that
for positive real numbers a and integers m and n, we can evaluate the first part:
![(8)^(2/3) = \sqrt[3]{8^2} = \sqrt[3]{64} =4](https://img.qammunity.org/2023/formulas/mathematics/high-school/d6kucdq3h6pnakfmb08we7w53zcx70g5yb.png)
For the second part, we use the power-to-a-power rule, that says
:
![\left(x^6\right)^(2/3) = x^{6\cdot (2)/(3)} = x^4](https://img.qammunity.org/2023/formulas/mathematics/high-school/po4rcyxnko2g17bg56rloe6nkvpo8cf0nq.png)
Putting that all together, we have
![\left(8 x^6\right)^(2/3) = \left(8\right)^(2/3) \cdot \left(x^6\right)^(2/3) = 4x^4](https://img.qammunity.org/2023/formulas/mathematics/high-school/54jye36ivj5xsyvukeluoqglivcap4ao2v.png)